Associations of understaffing and cardiovascular health of hospital care providers: A multi-source study. (November 2019) - Weigl, Matthias; Schmuck, Felix; Heiden, Barbara; Angerer, Peter; Müller, Andreas
Abstract: Background: Understaffing in hospitals is a serious problem in healthcare work since it jeopardizes efficiency, reliability and quality of care as well as the work life of the healthcare professionals. However, estimates on the associations of understaffing and cardiovascular health in healthcare professionals are lacking. Further shortcomings refer to the problem, that determinant and outcome measures are often assessed via self-reports what increases the risk of spurious estimates due to common source bias. Objective: We sought to reliably identify associations between understaffing and cardiovascular health in hospital nurses. Methods: Multi-source and cross-sectional study. N = 273 nurses of a large academic hospital were surveyed. All filled out a standardized questionnaire to report psychosocial work conditions and underwent a standardized medical examination. Cardiovascular health outcomes were blood pressure and blood cholesterol (total cholesterol level, LDL-cholesterol) as well as the SCORE classification. Logistic regression analyses were applied to calculate risk estimates for the understaffing and cardiovascular health relationship, adjusted for individual and life-style factors (e.g., sex, age, BMI, alcohol consumption, smoking) and work related characteristics (i.e., shift work, leadership position, work load, autonomy, social support at work). Results: Multivariate associations revealed significant relationships of perceived understaffing with increased blood pressure [OR = 1.60, 95% CI: 1.05, 2.43] and increased total cholesterol [OR = 1.42, 95 CI: 1.04, 1.95]. LDL cholesterol level was associated with understaffing. We furthermore observed associations of high autonomy and high cholesterol levels. Conclusions: Nurses in hospital units with lower staffing ratios had an increased risk for adverse cardiovascular health, irrespective of workload and social support. We discuss implications for future research on potential mechanisms of understaffing and nurses' health outcomes. The associated risks of poor nurse-patient-ratios for provider health need to be addressed through work and organizational design efforts.